Autoclave Sterilization of PEDOT:PSS Electrophysiology Devices. Issue 24 (25th November 2016) - Uguz, Ilke; Ganji, Mehran; Hama, Adel; Tanaka, Atsunori; Inal, Sahika; Youssef, Ahmed; Owens, Roisin M.; Quilichini, Pascale P.; Ghestem, Antoine; Bernard, Christophe; Dayeh, Shadi A.; Malliaras, George G.
Abstract : Autoclaving, the most widely available sterilization method, is applied to poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) electrophysiology devices. The process does not harm morphology or electrical properties, while it effectively kills E. coli intentionally cultured on the devices. This finding paves the way to widespread introduction of PEDOT:PSS electrophysiology devices to the clinic.